Development of Flascard Media Based on the Canva Application for Letter Recognition for 5-6 Year Olds in Sinunukan District, Mandailing Natal Regency - Suparni Suparni; Weni Yulastri; Siti Aisyah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This research aims to develop a learning medium in the form of flashcards based on the Canva app to introduce letters to children aged 5-6 years. The background of this research is the low interest in learning letters in children and the limited availability of interactive and engaging learning media. The Canva app was chosen because of its ease of creating engaging visual designs, which is expected to increase children's motivation and active participation in the learning process. The research method used was Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The analysis phase was conducted to identify the needs of children and teachers. The design phase included developing a flashcard concept that suited the developmental characteristics of children. The development phase focused on creating flashcards using Canva. The implementation phase involved testing the media on children aged 5-6 years. The evaluation phase was conducted to measure the effectiveness and feasibility of the developed media. The research results show that this Canva-based flashcard media is highly feasible and effective for use. Trials demonstrated significant improvements in children's letter recognition skills. The practicality of the trial showed that teacher responses achieved a score of 92.5%, and children's responses achieved a score of 90.71%. This media is recommended as an alternative, innovative learning tool for improving basic literacy skills in early childhood.